Enhancer elements upstream of the SHOX gene are active in the developing limb - Durand, Claudia; Bangs, Fiona; Signolet, Jason; Decker, Eva; Tickle, Cheryll; Rappold, Gudrun (European journal of human genetics, 2010)
Léri-Weill Dyschondrosteosis (LWD) is a dominant skeletal disorder characterized by short stature and distinct bone anomalies. SHOX gene mutations and deletions of regulatory elements downstream of SHOX resulting in haploinsufficiency have been found in patients with LWD. SHOX encodes a homeodomain transcription factor and is known to be expressed in the developing limb. We have now analyzed the regulatory significance of the region upstream of the SHOX gene. By comparative genomic analyses, we identified several conserved non-coding elements, which subsequently were tested in an in ovo enhancer assay in both chicken limb bud and cornea, where SHOX is also expressed. In this assay, we found three enhancers to be active in the developing chicken limb, but none were functional in the developing cornea. A screening of 60 LWD patients with an intact SHOX coding and downstream region did not yield any deletion of the upstream enhancer region. Thus, we speculate that SHOX upstream deletions occur at a lower frequency because of the structural organization of this genomic region and/or that SHOX upstream deletions may cause a phenotype that differs from the one observed in LWD.